Al-Rasm al-'Uthmānī fī al-Muṣḥaf al-mi‘yārī al-Indūnīsī ‘inda al-Dānī wa Abī Dāwud - Madzkur, Zainal Arifin (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2020)
This article aims to find a scientific argument for the differences in rasm ‘Uthmānī between Indonesian’s muṣḥaf and Madinah’s muṣḥaf. Some people claim that rasm ‘Uthmānī of the Madinah’s muṣḥaf is the most proper compared to the Indonesian’s muṣḥaf. Through the comparison of the differences in both muṣḥafs based on the two books of al-Muqni‘ by al-Dānī and Mukhtaṣar al-tabyīn by Abū Dāwud Sulaymān, both have basics of similarity. The difference in the writing of rasm ‘Uthmānī in the Indonesian’s muṣḥaf and the Madinah’s muṣḥaf in general only lies in the difference in their affiliation in the two major schools in this discipline that were written in the 5th century Hijri by al-Dānī and Abū Dāwud. This article proves that differences in rasm ‘Uthmānī are common in terms of transmission, and the claim that the rasm of Madinah’s muṣḥaf is the most correct of rasm ‘Uthmānī is a mistake.